Identification of biomarkers for tuberculosis disease using a novel dual-color RT–MLPA assay - Joosten, S A; Goeman, J J; Sutherland, J S; Opmeer, L; de Boer, K G; Jacobsen, M; Kaufmann, S H E; Finos, L; Magis-Escurra, C; Ota, M O C; Ottenhoff, T H M; Haks, M C (Genes and immunity, 2012)
Owing to our lack of understanding of the factors that constitute protective immunity during natural infection with Mycobacterium tuberculosis ( Mtb ), there is an urgent need to identify host biomarkers that predict long-term outcome of infection in the absence of therapy. Moreover, the identification of host biomarkers that predict (in)adequate response to tuberculosis (TB) treatment would similarly be a major step forward. To identify/monitor multi-component host biomarker signatures at the transcriptomic level in large human cohort studies, we have developed and validated a dual-color reverse-transcriptase multiplex ligation-dependent probe amplification (dcRT–MLPA) method, permitting rapid and accurate expression profiling of as many as 60–80 transcripts in a single reaction. dcRT–MLPA is sensitive, highly reproducible, high-throughput, has an extensive dynamic range and is as quantitative as QPCR. We have used dcRT–MLPA to characterize the human immune response to Mtb in several cohort studies in two genetically and geographically diverse populations. A biomarker signature was identified that is strongly associated with active TB disease, and was profoundly distinct from that associated with treated TB disease, latent infection or uninfected controls, demonstrating the discriminating power of our biomarker signature. Identified biomarkers included apoptosis-related genes and T-cell/B-cell markers, suggesting important contributions of adaptive immunity to TB pathogenesis.